Effectiveness of a Novel Augmented Reality-Based Navigation System in Treatment of Orbital Hypertelorism. Issue 6 (December 2016) - Zhu, Ming; Chai, Gang; Lin, Li; Xin, Yu; Tan, Andy; Bogari, Melia; Zhang, Yan; Li, Qingfeng
Abstract : Background: Augmented reality (AR) technology can superimpose the virtual image generated by computer onto the real operating field to present an integral image to enhance surgical safety. The purpose of our study is to develop a novel AR-based navigation system for craniofacial surgery. We focus on orbital hypertelorism correction, because the surgery requires high preciseness and is considered tough even for senior craniofacial surgeon. Methods: Twelve patients with orbital hypertelorism were selected. The preoperative computed tomography data were imported into 3-dimensional platform for preoperational design. The position and orientation of virtual information and real world were adjusted by image registration process. The AR toolkits were used to realize the integral image. Afterward, computed tomography was also performed after operation for comparing the difference between preoperational plan and actual operational outcome. Results: Our AR-based navigation system was successfully used in these patients, directly displaying 3-dimensional navigational information onto the surgical field. They all achieved a better appearance by the guidance of navigation image. The difference in interdacryon distance and the dacryon point of each side appear no significant ( P > 0.05) between preoperational plan and actual surgical outcome. Conclusions: This study reports on an effective visualized approach for guiding orbital hypertelorism correction. Our AR-based navigation system may lay a foundation for craniofacial surgery navigation. The AR technology could be considered as a helpful tool for precise osteotomy in craniofacial surgery.